Assessment of Ground Conditions Near a Mine Portal Using Ground Penetrating Radar - Michael Trevits (International Conference on Ground Control in Mining, 2005)
The NIOSH Lake Lynn Laboratory (LLL) is a unique research facility, located about 50 miles southeast of Pittsburgh, Pennsylvania, that is designed to provide a full-scale mining environment for testing and evaluation of mine health and safety technologies. The LLL occupies more than 400 acres and is composed of surface test and training areas and an underground mine. The Lake Lynn Experimental Mine (LLEM) was built at an abandoned commercial limestone quarry where surface mining ceased in the late 1960's. Later, new underground development was constructed to simulate modern-day coal mining scenarios; including room-and-pillar and longwall mining layouts. In January 1994, a sinkhole opened southeast of the No. 4 Portal of the LLEM and since then, the area of the underground failure and surface deformation has continued to expand and now includes several interconnected sinkholes. A concern developed that the overburden instability could expand and affect the structural integrity of the nearby highwall and the No. 4 Portal. It was unsafe to conduct a detailed underground survey of the mine in this area because the mine roof conditions near the No. 4 Portal had deteriorated significantly. It was decided to investigate the overburden conditions near the No. 4 Portal using ground penetrating radar (GPR). A GPR survey grid was located along an access road that passes over the top of the portal. To delineate the mine conditions near the portal, antennas whose frequency spectra produced pulses centered near 100- and 200-MHz were used. The results of the GPR survey suggests that the overburden rock units appear to be laterally consistent to a depth of about 15-ft. Below that point, the overburden appears to be significantly disturbed and it was hypothesized that this area contains a large roof fall. A follow-up ground truth survey of the mine roof conditions was conducted from the mouth of the portal. It is concluded that the observations and measurements made from the radar records appear to be correct as a large roof fall was observed and measured from the mine portal area.